Disgust sensitivity predicts political ideology and policy attitudes in the Netherlands. (15th November 2014) - Brenner, Corinne J.; Inbar, Yoel
Abstract Individual differences in disgust sensitivity have been linked to social attitudes and ideology, but the generalizability of this effect and the nature of the political issues implicated remain unclear. In two studies using large Dutch samples, we find that disgust sensitivity predicts political attitudes for issues in several domains related to physical/spiritual purity and pathogen risk. Sensitivity to disgust was significantly associated with attitudes for a general 'physical and spiritual purity' factor, as well as specific issue factors regarding sex and sexual minorities, immigration, and foreign outgroups. Additionally, disgust sensitivity was associated with greater likelihood of voting for the socially conservative "Freedom Party" (Partij Voor de Vrijheid). These results suggest that the tendency to experience disgust influences a specific subset of social and political attitudes across cultures. Copyright © 2014 John Wiley & Sons, Ltd.